Enhanced visible light driven photocatalytic and antibacterial activities of Ag2WO4 decorated ZnS nanocomposite. Issue 9 (1st May 2021) - Kokilavani, S.; Al-Farraj, Saleh A.; Thomas, Ajith M.; El-Serehy, Hamed A.; Raju, Lija L.; Khan, S. Sudheer
Abstract: Our research demonstrates an improved visible light driven photocatalytic and anti-microbial activity of ZnS/Ag2 WO4 nanocomposite (NCs). ZnS/Ag2 WO4 NCs was synthesized via chemical co-precipitation method and the characterization was done by using UV–vis DRS, EDAX, XRD, XPS, FTIR, PL, HR-TEM, and N2 adsorption-desorption. The crystalline nature and co-existence of ZnS and Ag2 WO4 NPs were verified by HRTEM, XRD and SAED analysis. The EDAX and XPS validate the presence of Ag, W, O, Zn and S. On comparison of ZnS/Ag2 WO4 with pure ZnS (3.52 eV), its band gap was shifted to 3.1 eV which enhanced the photocatalytic performance in visible region. The investigation of mechanism of methylene blue degradation by NCs was performed by scavenging test. The results suggests that hydroxyl radicals as the key species responsible for the photodegradation of MB. The photocatalytic degradation using ZnS/Ag2 WO4 (3 mg/L) reached 84% after 140 min. The pseudo-first-order kinetics suits well with MB degradation providing a good correlation coefficient values (R 2 > 0.92) and it was fitted to the Langmuir–Hinshelwood model. XRD spectra of recycled ZnS/Ag2 WO4 remains same as prepared one indicates its resistance against photo-corrosion. The ZnS/Ag2 WO4 NCs showed excellent photocatalytic degradation efficiency compared to that of bare ZnS NPs and Ag2 WO4 NPs. The NCs exhibits a broad-spectrum antibacterial property against E. coli (gram -ve bacteria) and B. subtilis (gram +ve bacteria). The novel ZnS/Ag2 WO4 could be used as an efficient photocatalysts for the toxic pollutant degradation under visible light and as potent antibacterial agent.